2012
DOI: 10.1590/s0066-782x2012005000040
|View full text |Cite
|
Sign up to set email alerts
|

Estudo das alterações ecocardiográficas nos primeiros seis meses após o transplante renal

Abstract: Background: Cardiac disorders are very common in individuals with chronic kidney disease and are associated with morbimortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[ 11 14 15 27 ] Similarly, diastolic function had also been shown to improve following transplantation in four studies. [ 24 26 27 29 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 11 14 15 27 ] Similarly, diastolic function had also been shown to improve following transplantation in four studies. [ 24 26 27 29 ]…”
Section: Methodsmentioning
confidence: 99%
“…One study, assessing 50 individuals before and 3 months after renal transplantation, de­monstrated significant improvement of the ejection fraction and reduction of the chamber diameters [12]. This increase is reported in other studies as well [10, 13, 14]. …”
Section: Discussionmentioning
confidence: 61%
“…It is reported that successful renal transplantation has positive effects on ventricular hypertrophy and could regress LVH and improve LVEF during the first year after transplantation [6-10]. …”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular ejection fraction has been shown to be a better predictor [ 10 ] of posttransplant outcomes. It is often felt that the uremic milieu, volume overload, and chronic anemia contribute to the underlying dysfunction and that cardiac function may improve with transplantation [ 12 ]. Studies by Sharma et al [ 13 ] have suggested that a reliable assessment of preoperative cardiac disease would utilize dobutamine stress echocardiogram.…”
Section: Prevention and Treatment Of Cardiovascular Disease In Renal mentioning
confidence: 99%